2019
DOI: 10.1136/bmjopen-2018-024459
|View full text |Cite
|
Sign up to set email alerts
|

“You can smell the freedom”: a qualitative study on perceptions and experiences of sex among Swedish men who have sex with men in Berlin

Abstract: PurposeThe purpose of this study was to explore the perceptions and experiences of sex among Swedish Men who have Sex with Men (MSM) in Berlin.BackgroundMSM are disproportionally affected by HIV.Berlin is also a key destination when looking into where Swedish MSM sero-convert, while travelling.MethodA qualitative study with semi-structured interviews using open-ended questions with participants recruited through network sampling. Data were analysed with content analysis.Participants15 Swedish cis-men (as in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…In a statement from 2016, the Public Health Agency of Sweden advised against the use of HIVST, based on the argument that testing opportunities in the country are adequate and that HIVST leads to missed opportunities for counseling and testing for other STIs [ 27 ]. While previous studies and reports have investigated the prevention needs and preferences among Swedish MSM [ 15 , 28–33 ], no previous studies concerning self-test in the Swedish setting have been identified by the authors. A greater understanding of prevention preferences enables decision makers to make informed policy decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In a statement from 2016, the Public Health Agency of Sweden advised against the use of HIVST, based on the argument that testing opportunities in the country are adequate and that HIVST leads to missed opportunities for counseling and testing for other STIs [ 27 ]. While previous studies and reports have investigated the prevention needs and preferences among Swedish MSM [ 15 , 28–33 ], no previous studies concerning self-test in the Swedish setting have been identified by the authors. A greater understanding of prevention preferences enables decision makers to make informed policy decisions.…”
Section: Introductionmentioning
confidence: 99%
“…However, while cases of persons who intentionally infected others with HIV made the news in several Western European countries [ 94 , 95 ] it has never been examined whether these reports have influenced people’s attitudes about others with HIV. Moreover, in Sweden specifically, these cases have tended to revolve around heterosexual men [ 7 , 67 , 71 , 96 , 97 ] spreading the virus to women, while HIV is predominantly found in gay men and other MSM. As such, while intentional transmission of HIV has been deemed a criminal act without bias, at large such policies have mostly come to affect the MSM population—or even persons completely unaware of their HIV status [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…This research is part of a larger qualitative project exploring travel, drug use and sexual health among highly sexually active Swedish MSM who spend time in both Sweden and Berlin [64,65].…”
Section: Methodsmentioning
confidence: 99%